Morphological spore-based characterisation and molecular approaches reveal comparable patterns in glomeromycotan communities - Cofré, Noelia; Grilli, Gabriel; Marro, Nicolás; Videla, Martín; Urcelay, Carlos (Mycorrhiza, 2025)
Traditionally, characterisation and comparison of AMF communities has been carried out by morphological identification of asexual spores in soil. In recent decades, molecular methods such as soil metabarcoding have become more popular than morphological identification of spores, but direct comparisons of the efficiency of both approaches have been rare. In this study, we compared AMF communities in soil samples from vegetable farms using both morphological and molecular methods (internal transcribed spacer, ITS, markers). In addition, we performed a systematic literature search and retrieved nine studies that analysed AMF communities using both approaches in the same soil samples, mostly in agroecosystems. Our results show that AMF communities determined by morphological spore-based identification are different than those determined by molecular genetic markers, but not as often claimed. In some cases, the morphological spore-based characterisation of spores revealed more diverse glomeromycotan communities. Moreover, in several cases the spore-based methods recovered taxa that the molecular methods did not, while in other cases the opposite was observed. The field and literature-based results of this study indicate that for a comprehensive and exhaustive characterisation of AMF communities it is necessary to combine both approaches. However, if the aim is to compare communities under different environmental conditions, both approaches provide comparable patterns.
Keywords: DNA fungální; Spores, Fungal; spory hub; mezerníky ribozomální DNA; DNA, Fungal; Crop management; Agroecology; Glomeromycota; Methods in AMF studies; mykorhiza; DNA, Ribosomal Spacer; Morphospecies ASVs; Mycorrhizae; půdní mikrobiologie; Soil Microbiology